Autopromotion of K-Ras4B Feedback Activation Through an SOS-Mediated Long-Range Allosteric Effect - He, Xuan; Du, Kui; Wang, Yuanhao; Fan, Jigang; Li, Mingyu; Ni, Duan; Lu, Shaoyong; Bian, Xiaolan; Liu, Yaqin (Frontiers in Molecular Biosciences, 2022)
The Ras-specific guanine nucleotide exchange factors Son of Sevenless (SOS) regulates Ras activation by converting inactive GDP-bound to active GTP-bound states. The catalytic activity of Ras is further allosterically regulated by GTPRas bound to a distal site through a positive feedback loop. To address the mechanism underlying the long-range allosteric activation of the catalytic K-Ras4B by an additional allosteric GTP–Ras through SOS, we employed molecular dynamics simulations of K-Ras4BG13D•SOScat complex with and without an allosteric GTP-bound K-Ras4BG13D. We found that binding of an allosteric GTPK-Ras4BG13D enhanced the affinity between the catalytic K-Ras4BG13D and SOScat, forming a more stable conformational state. The peeling away of the switch I from the nucleotide binding site facilitated the dissociation of GDP, thereby contributing to the increased nucleotide exchange rate. The community networks further showed stronger edge connection upon allosteric GTPK-Ras4BG13D binding, which represented an increased interaction between catalytic K-Ras4BG13D and SOScat. Moreover, GTPK-Ras4BG13D binding transmitted allosteric signaling pathways though the Cdc25 domain of SOS that enhanced the allosteric regulatory from the K-Ras4BG13D allosteric site to the catalytic site. This study may provide an in-depth mechanism for abnormal activation and allosteric regulation of K-Ras4BG13D.